(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2014)
Before marketing a cosmetic product, a series of biological assays, such as ocular irritation tests, must be conducted in order to prove that the product is safe. However, a few scientific articles mention the discussion and evolution of cosmetic products testing performed in the eyes area. The aim of this study was to review the available literature on the evolution of tests carried out with cosmetics, in the ocular area, as well as to describe the methodologies that have been used and that are currently accepted. In Brazil, tests performed on animals are still allowed. However, the international laws strongly recommend the use of alternative methods for evaluating the risk of cosmetic ingredients and products. Regulatory requirements involving the registration of these products also request safety support of them in human beings. To perform ocular tests in human beings, it is necessary to involve an ophthalmologist for conducting clinical protocols. These protocols signed by the expert physician are sent to the National Health Surveillance Agency in order to endorse the product manufacturer concerning its safety. The safety support of a cosmetic product is very important, taking into account that the consumer has free access to these products of widespread use in today's society.